Curative effect of auricular copper scraping combined with auricular acupoint pressing on insomnia after Methylprednisolone pulse therapy for thyroid-associated ophthalmopathy (耳部铜砭刮痧联合耳穴贴压对甲状腺相关性眼病激素冲击治疗后失眠的疗效观察) - MA Yan (马艳); ZHAO Yue (赵悦); LIN Yuxiao (林育潇); LIU Xiao (刘笑); SONG Yumin (宋玉敏) (中西医结合护理)
Objective　Methods 82 patients diagnosed with thyroid-associated ophthalmopathy who needed hormone pulse therapy were randomly divided into control group and observation group according to numerical method, with 41 cases in each group. Patients in both groups were given methylprednisolone pulse therapy. The control group was given conventional symptomatic treatment, and the observation group was given auricular copper acupuncture scraping and auricular acupoint pressing treatment on the basis of the control group. The sleep condition, Pittsburgh Sleep Quality Index (PSQI) and Self-rating Anxiety Scale (SAS) of the two groups were compared. Results Two patients dropped out of the study. The effective rate of sleep improvement in observation group was 87. 18%(34/39), which was significantly higher than 41. 46%(17/41) in control group (P < 0. 05). The PSQI of the observation group was significantly lower than that of the control group (P < 0. 05). The score of SAS scale in the control group was (54. 95±2. 30), and was (51. 16±4. 35) in the observation group, with a significant difference (P<0. 05). Conclusion Auricular copper scraping combined with auricular acupoint pressing therapy is potentially effective to improve the sleep quality, prevent the occurrence of complications, and promote the recovery of patients with insomnia after Methylprednisolone pulse therapy for thyroid-associated ophthalmopathy. Totally　To investigate the curative effect of auricular copper scraping combined with auricular acupoint pressing on insomnia after Methylprednisolone pulse therapy for thyroid-associated ophthalmopathy. (目的 探讨耳部铜砭刮痧联合耳穴贴压对甲状腺相关性眼病激素冲击后失眠的疗效观察。方法 选取82例确诊为甲状腺相关性眼病且需要行激素冲击治疗的患者, 按照数字法随机分为对照组和观察组, 各41例。两组患者均给予注射用甲泼尼龙琥珀酸钠(甲强龙)冲击治疗。对照组给予常规对症治疗, 观察组在对照组的基础上给予耳部铜砭刮痧和耳穴贴压治疗。比较两组患者的睡眠情况改善情况、匹兹堡睡眠质量指数(PSQI)、焦虑自评量表(SAS)评分。结果 观察组2例患者退出研究。观察组睡眠状况改善有效率87. 18%(34/39), 高于对照组的41. 46%(17/41), 差异有统计学意义(P＜0. 05)。观察组患者PSQI评分低于对照组, 差异有统计学意义(P＜0. 05); 观察组患者SAS量表评分(51. 16±4. 35)分, 低于对照组的(54. 95±2. 30)分, 差异有统计学意义(P＜0. 05)。结论 耳部铜砭刮痧配合耳穴贴压能够改善甲状腺相关性眼病激素冲击治疗后的睡眠状况, 预防并发症发生, 促进患者康复。)